Pembelajaran pendidikan jasmani adaptif: Minat siswa tunarungu dalam pembelajaran daring di masa pandemi COVID-19 - Sari, Merlina; Risma, Nova; Ulfa, Dery Anggita (Edu Sportivo: Indonesian Journal of Physical Education, 2021)
During the Covid-19 pandemic, adaptive physical education teachers in carrying out online learning experienced many obstacles, resulting in decreased interest in learning. The purpose of this study was to determine students' interest in online learning in adaptive physical education subjects at the Kartama Kasih Ibu Special Junior High School Pekanbaru. This type of research is descriptive quantitative. The population in this study was students who were deaf at SMPLB Kartama Kasih Ibu Pekanbaru, amounting to 47 students. The sampling technique is systematic sampling with a sample of 45 students. The indicators of interest in the questionnaire were divided into 4 indicators, namely: 1) feelings of pleasure, 2) student interest, 3) attention, 4) student involvement. The number of initial statements designed is 60 statement items and after being tested for validity it becomes 44 statement items. The results of this study are student interest in online learning in adaptive physical education subjects at Kartama Kasih Ibu Special Junior High School Pekanbaru with an average of 78.5% in the good category. It is hoped that with this research, students will continue to increase their interest in adaptive physical education subjects, because these subjects are one of the important subjects that have benefits for physical fitness.